Observation of a unique storm-time VLF chorus emissions at low latitude Indian ground station Jammu (L= 1.17) - Singh K.K. (My University, 2025)
This paper summarizes a unique observation of storm-time VLF chorus emissions obtained during investigation of VLF data collected over a period of about one year at our low latitude ground-based Indian station Jammu (geomag. lat., 22 deg 26 min North, L= 1.17) in order to connect the peculiarities of this ground-observed VLF chorus with the plasma processes in the magnetosphere during geomagnetic disturbances. The upper boundary frequency method (UBF-method) based on the measurement of the upper boundary frequency of the ground-observed chorus is used for the determination of the location of the source of storm-time chorus emissions observed at our ground station Jammu. Dynamics of chorus spectra of the emissions observed at Jammu on 18 February 1998 in daytime during magnetic storm period are investigated in detail in order to solve the physics of the ground-observed chorus emissions at low latitudes. To explain various temporal and spectral features of storm-time VLF chorus emissions observed at Jammu, a generation mechanism based on the backward wave oscillator (BWO) regime of the magnetospheric cyclotron maser has been presented. Using BWO model, the calculation of some magnetospheric parameters such as plasma density, large-scale electric field etc. are carried out. The conformity between the calculated and typical measured parameters is shown and discussed. Finally the conclusion of this study is reported. © 2017, Springer Science+Business Media Dordrecht.